Pengaruh Strategi dan Preferensi Investor terhadap Pengambilan Keputusan Investasi dengan Media Informasi sebagai Variabel Moderating - Isabelle Imelda; Elizabeth Lucky Maretha Sitinjak; Eny Trimeiningrum (Jurnal Pasar Modal dan Bisnis, 2019)
The purpose of this study was to determine the effect of investor strategies and preferences on investment decision making with information media as a moderating variable. The population in this study are all investors in Semarang. The sampling technique in this study used purposive sampling technique. Data from this study are derived from primary data. The method used for data collection needed in this study is a questionnaire. Data analysis in this study uses multiple regression analysis. The results of this study are that investor strategy has a positive effect on investment decision making, investor preferences have a positive effect on investment decision making, information media can be a moderating variable that strengthens the influence of investor strategy on investment decision making, but it is not significant, and information media can be a moderating variable that is strengthen the influence of investor preferences on investment decision making.